Budgetpolitik im Zeitalter verminderter Erwartungen - Markus Marterbauer (Austrian Institute of Economic Research (WIFO), 2010)
– The concept of debit and credit balances implies that the state's financing deficit can be reduced only when the business sector and the foreign sector at the same time assume more debts or when private households reduce their surplus. This working paper investigates how economic policy can influence such adjustments in an "age of reduced expectations" and low GDP growth rates. Considering the low capacity utilisation there is little likelihood of a debt-financed upswing of private investment. Greater demand from abroad, which could give rise to an export-oriented strategy of consolidation, could be seriously dampened by the simultaneous budget consolidation efforts in all EU countries. During the crisis savings rose as a proportion of the disposable incomes of private households, and there are several strategies to cut this rate again: 1. A credit-financed housing price bubble was used by several countries in recent years, but was found to be a macroeconomic disaster. 2. In a period of weak economic growth, high unemployment and thus precautionary saving can be effectively reduced by an increase of the employment elasticity of growth and a reduction of actual working hours. 3. Another promising approach is to improve incentives for the top income groups to increase their investment spending and cut down on their savings. 4. Redistributing assets and incomes leads to a dip in the average propensity to save and an increase of the demand for consumption among private households.
Keywords: 330; Haushaltsdefizit; Konjunktur; Haushaltskonsolidierung; Sparen; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; Österreich